Optimalisasi Zakat dan Wakaf melalui Inovasi Digital dalam Rangka Maqashid Syariah: Solusi Pengentasan Kemiskinan di Indonesia - Mokhammad Ainur Rofiq; Joharul Fathoni; Najhah Barnamij (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study aims to evaluate the role of zakat and waqf as Islamic philanthropy tools for poverty alleviation and sustainable development in Indonesia, integrating maqāṣid al-sharīʿah principles with digital innovation. Employing a descriptive-critical qualitative approach with data triangulation, it analyses empirical data from official reports and recent literature. Findings demonstrate that zakat distribution significantly reduces poverty, while productive waqf enhances access to education and health services. However, institutional constraints, limited nazhir capacity, and technological barriers—particularly in rural areas—hinder effectiveness. Comparative insights from Malaysia, Turkey, and Saudi Arabia highlight best practices in digital zakat and waqf management, such as blockchain adoption and centralized waqf registries, which inform the contextual framework proposed for Indonesia. The study advocates a holistic approach combining maqāṣid al-sharīʿah with digitalization, supported by synergy among government, philanthropic institutions, and local communities.